Fracture and flow in natural rock deformation - Mancktelow, N. S. (TRABAJOS DE GEOLOGÍA, 2009)
Field observation shows that brittle fracturing and ductile flow are often intimately related under a wide range of metamorphic conditions. By their very nature, brittle fractures tend to be discrete and ductile flow more distributed, so that strong localization is often more readily attributed to brittle fracture or to subsequent ductile reactivation of a brittle precursor. Brittle fractures commonly show little regard for existing compositional boundaries and can crosscut them at a low angle, whereas ductile localization is typically bound to bands of different composition and/or rheology. Very localized regional fault zones can extend for hundreds of kilometres with widths on the order of hundreds of metres or less. They commonly crosscut many different compositional units at low angles, which suggests a potential brittle precursor to the mylonite zone now observed. In general, ductile viscous flow initially localized on discrete compositional or rheological precursors may actually tend to broaden rather than localize with time. The interplay between brittle fracture and localized viscous flow in shear zones, and the associated tectonic pressure effects relative to the adjacent matrix, are critical for understanding fluid flow in heterogeneously deforming rocks and thus for the interpretation of veins, fluid-rock interaction, migmatites and melt accumulation.